Experimental infection of shrews (Crocidura russula) with Borna disease virus 1 : insights into viral spread and shedding - Nobach, Daniel; Raeder, Leif; Müller, Jana; Herzog, Sibylle; Eickmann, Markus; Herden, Christiane; Justus Liebig University Giessen (My University, 2025)
Numbers of human encephalitis cases caused by infection with Borna disease virus 1 (BoDV1) increase continuously in endemic areas. The reservoir host of BoDV1 is the bicolored white-toothed shrew, albeit few naturally infected individuals of other shrew species have been detected. To establish a reliable experimental reservoir model, 15 greater white-toothed shrews were infected with a shrew-derived BoDV1 isolate by different inoculation routes (intracerebral, intranasal, oral, subcutaneous, and intraperitoneal) and monitored up to 41 days. Except for the oral route, all other animals (12/15) were successfully infected, and the majority of them displayed temporarily reduced feed intake and loss of body weight but no inflammatory lesions. Infectious virus was isolated from 11/12 infected animals. Viral RNA was demonstrated by qRT-PCR in the central nervous system (CNS) and the majority of organs. Immunohistochemistry demonstrated BoDV1 antigen in neurons and astrocytes in the CNS and peripheral nerves. High viral loads in the CNS and the spinal cord points towards spread from periphery to the CNS to enhance viral replication and subsequent centrifugal spread to organs capable of secretion and excretions. In general, successful experimental BoDV1 infection of shrews proves their usefulness as animal model, enabling further studies on maintenance, transmission, pathogenesis, and risk assessment for human spillover infections.
Keywords: ddc:630